Factors Influencing the Overall Motivation of Women towards Entrepreneurship: A Study Conducted in Meerut City (UP), India (Global Journal of Management and Business Research, 2022)
This paper highlighted the significance of various factors influencing the overall motivation of women towards entrepreneurship. The study was based on the empirical study conducted in Meerut City in western UP, India.
Keywords: overall motivation; women entrepreneurship; meerut city; extra income generation; social recognition